2021
DOI: 10.1007/s11686-021-00461-w
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Paragonimus skrjabini Complex from Yunnan, China: A Brief Report

Abstract: Purpose To perform environmental sampling and molecular identification of Paragonimus in endemic regions, which may help in minimizing transmission among humans. Methods Mountain crabs from the genus Potamiscus were collected and the encysted metacercariae were extracted and subjected to morphological identification, followed by animal inoculation in Sprague–Dawley (SD) rats. After 112 days of infection, animals were killed and adult worms were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Phylogenetic studies revealed that there exists a P. skrjabini complex, which includes P. skrjabini, P. skrjabini miyazakii and P. proliferus (syn. P. hocuoensis ) (Doanh et al ., 2013b ; Yang et al ., 2021 ; Shu et al ., 2021 a ). P. skrjabini is now known to occur in China, Thailand, Vietnam and northeast India (Singh et al ., 2006 ; Doanh et al ., 2013b ; Blair, 2019 ).…”
Section: Lung Flukesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic studies revealed that there exists a P. skrjabini complex, which includes P. skrjabini, P. skrjabini miyazakii and P. proliferus (syn. P. hocuoensis ) (Doanh et al ., 2013b ; Yang et al ., 2021 ; Shu et al ., 2021 a ). P. skrjabini is now known to occur in China, Thailand, Vietnam and northeast India (Singh et al ., 2006 ; Doanh et al ., 2013b ; Blair, 2019 ).…”
Section: Lung Flukesmentioning
confidence: 99%
“…( 2015 ) reviewed 46 P. skrjabini miyazakii patients reported from 1974 to 2009 having pulmonary involvement. Phylogenetic studies revealed that P. skrjabini miyazakii is clearly included among the P. skrjabini complex (Blair et al ., 2005 ; Doanh et al ., 2013b ; Yang et al ., 2021 ; Shu et al ., 2021 a ; 2021 b ). Freshwater crabs, Geothelphusa dehaani carry the metacercariae (Blair et al ., 1999a ).…”
Section: Lung Flukesmentioning
confidence: 99%
“…taxonomy and systematic utilized morphological data during species characterization (Erlank et al 2018;Shu et al 2022). In some animal groups, morphology characteristics are entirely satisfactory (Chan et al 2016;Mauroka et al 2018;Korovchinsky 2019).…”
Section: Classicalmentioning
confidence: 99%